ANALISIS KETERAMPILAN PROSES SAINS MELALUI METODE PRAKTIKUM PADA MATERI LAJU REAKSI - Annisa Fadhilah; elvi yenti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2019)
AbstractThe background of this research is difficulty of understanding chemical concepts by students. The teacher-centered learning strategy causes students potential and abilities at learning activities in the classroom does not develope. This research aimed at analyzing how student science process skill at the eleventh grade of Natural Science through Practical Work method, analysis is the first step for teacher to develop process-oriented learning strategies. It was conducted at the eleventh-grade students of Natural Science on Reaction Rate lesson at the first semester in the Academic Year of 2018/2019, and it was administered at State Senior High School 2 Siak Hulu. It was a quantitative descriptive research. Purposive sampling technique was used in this research and the samples were 34 students. The instruments used to know student response and to strengthen the results of the obtained data were practicum performance instrument, essay test, and interview. The results of analyzing the data showed that student science process skill through Practical Work method overall was on enough category.  The highest aspect of the science process skill was observing with 53,3% mean percentage, and the lowest aspect is classification with 34% mean percentage. The highest aspect through essay test is communicating with 58.5% mean percentage, and the lowest aspect is classifying with 36.4% mean percentage. Keywords: Science Process Skill, Practical Work Method, Reaction Rate